Pengembangan Instrumen Penilaian Sikap Sosial Aspek Kerja Sama Pembelajaran Tematik Kelas IV SD - Heri Muftakim; Agustina Tyas Asri Hardini (Peneliti.net, 2021)
The purpose of this study is to develop an instrument for assessing the social attitude of the cooperative aspect of grade 4 elementary school students to determine the level of validation from experts or experts. the development of Research and Development (RnD) which was developed by Sukmadinata and has been adapted by Mawardi (2014: 93) consists of three stages, namely: 1) Preliminary Study; 2) Design and Development; and 3) Testing. The development model used is the ADDIE model which was developed by Raiser and Mollenda in the 1990s. According to Pribadi (in Subiyanti, 2013:27) the ADDIE model has 5 stages according to ADDIE, namely, analysis, design, development, implementation, evaluation. The process of developing the social attitude assessment instrument in the aspect of cooperation is carried out only until the expert validation test stage. This is due to the ongoing COVID-19 pandemic. Expert validation was carried out by 2013 curriculum assessment experts and PPKn material experts, each expert being a lecturer from the SWCU FKIP. The 2013 curriculum assessment expert gave a percentage of 86% with a very high category. While the PPKn material experts gave a percentage of 80% in the high category. Based on the value given by the experts, the instrument for assessing the social attitude of the cooperative aspect can be concluded that it is feasible to use after making improvements in accordance with the advice of the experts.